Study of composites properties based on modified sodium silicate - Шолух, Наталія Євгенівна (Eastern-European Journal of Enterprise Technologies, 2013)
The research in the field of interaction between inorganic binder (sodium silicate) and organic hardeners (dicarboxylic acid esters) has been conducted. The kinetics of saponification of several dicarboxylic acid esters in a sodium silicate medium has been studied. In this case, the kinetics of saponification is described by the pseudo-first order equation. The results of kinetic researches allow predicting the selection of dicarboxylic acid esters aimed at decreasing or increasing the prolonged action of esters depending on their structure and nature during organic-silicate composites structurization. Interrelation of structural properties of organic-inorganic composites components and physicochemical properties of coatings based on them has been shown. The hardeners effect on the properties of paint and adhesive composites has been verified. The improvement of operation properties when using the hardeners in organic-inorganic composites has been shown, namely increased paint coating water resistance and adhesive joint strength in adhesive composites. It is shown that the compounds containing ester groups can be used as hardeners of organic-inorganic composites.